Unlocking the therapeutic capabilities of GPCR in the treatment of ischemic stroke: A translational literature - Girish B S, Pharm.D; Nikitha B S, Pharm.D; Roopa K, Pharm.D; Meghana C S, Pharm.D; Srinivasan R, M.Pharm, PhD (Elsevier, 2024)
GPCRs are a class of membrane proteins that are essential to signal transduction, and this is a vital process in many different physiologies. The significant mortality rate and widespread occurrence of stroke highlight the need to accelerate the research to develop viable treatment agents. A promising prospect for the development of new treatment approaches is the increasing comprehension of the pathophysiology of stroke and the crucial roles played by GPCRs. Because of the blood clot, the glial cells' vascular supply is abruptly cut off, which sets off a series of events that include inflammation and neuronal damage and ultimately lead to cell death. Numerous therapeutic treatments, including thrombolytic agents like tissue plasminogen activator and urokinase, have been discovered as potential neuroprotective medicines; however, their use is restricted because of the modest therapeutic window. Accepting that GPCRs are the pertinent factors in ischemic stroke, we explore the potential medicinal promise of GPCR-targeted treatments and the shortcomings that ought to be resolved in order to translate these discoveries to clinical cases.